1987
DOI: 10.1111/j.0954-6820.1987.tb01249.x
|View full text |Cite
|
Sign up to set email alerts
|

Antacid Treatment of Duodenal Ulcer

Abstract: ABSTRACT. Becker U, Lindorff K, Andersen C, Ranløv PJ (Department of Internal Medicine B, Central Hospital, Hillerød, Denmark). Antacid treatment of duodenal ulcer. Acta Med Scand 1987; 221:95–101. Sixty‐seven consecutive outpatients with endoscopically verified duodenal ulcer were randomised to a double‐blind treatment with either 10 ml of an antacid suspension (buffering capacity 85 mmol/10 ml, packed in single dosage pads) 1 and 3 h after each meal and at bedtime or cimetidine 400 mg b.i.d. The double‐dumm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
0
1
Order By: Relevance
“…Adherence to treatment is much higher when a drug can be taken once daily [2,5,[10][11][12][13]. Studies have shown that a reduction from a dose of 3 or more times daily to once or twice daily significantly improves patient compliance [14][15][16][17][18]. In the present study, there was no relationship between adherence and dosing frequency (data not shown) before the switch from tablets to granules.…”
Section: Discussioncontrasting
confidence: 49%
“…Adherence to treatment is much higher when a drug can be taken once daily [2,5,[10][11][12][13]. Studies have shown that a reduction from a dose of 3 or more times daily to once or twice daily significantly improves patient compliance [14][15][16][17][18]. In the present study, there was no relationship between adherence and dosing frequency (data not shown) before the switch from tablets to granules.…”
Section: Discussioncontrasting
confidence: 49%